Application of logistic models for stock market bubbles analysis - Girdzijauskas, Stasys; Štreimikienė, Dalia (Journal of Business Economics and Management, 2009)
The article deals with economic bubbles and analyses their possible causes and tools for the prediction of such bubbles development. An economic bubble is the commonly used term for an economic cycle that is characterized by a rapid expansion followed by a dramatic crash. While some bubbles happen naturally as a part of the economic cycle, some also occur as a result of investor exuberance and serve as correctives. These typically happen in securities, stock markets, real estate and various other business sectors because of certain changes in the way key players conduct business. The well‐known and widely discussed bubbles in asset markets were analysed and compared trying to define the main features, causes and signals of such bubbles creation: Dotcom, Telecom, Health South Corporation, NASDAQ, etc. These bubbles were analysed in the article by applying the logistic growth model allowing to predict the bubbles creation as a result of growth satiation in the conditions of limited resources.First Publish Online: 14 Oct 2010